Pengaruh Kualitas Kehidupan Kerja dan Kompetensi terhadap Komitmen Organisasional Pegawai Negeri Sipil di Kantor Kecamatan Sunggal - Emia Pepayosa Br Pinem; Sahat P. Remus Silalahi; Kristanty M. N. Nadapdap (Universitas Methodist Indonesia, 2024)
The results showed that the variable quality of work life has a significant effect on organizational commitment, the value of tcount > ttable (3.359 > 1.991), then H1 is accepted, meaning that partially the quality of work life affects organizational commitment. The competency variable has a significant effect on organizational commitment, the value of tcount > ttable (3.154 > 1.991), then H1 is accepted, meaning that partially competence has an effect on organizational commitment. Together, the variables of quality of work life and competence affect organizational commitment, the value of Fcount > Ftable (18.035 > 3.11), then H1 is accepted, meaning that simultaneously the quality of work life and competence affect organizational commitment. Based on the conclusions above, it is recommended that the company make an effort to maintain organizational commitment by improving the quality of employee work life, and increasing competence so that every employee is competent in carrying out their duties.